A Biostimulant Based on Ilex paraguariensis Modulates Phytohormonal and Antioxidant Responses under High Temperatures in Cucumis melo L - Melisa E. Yonny; María Luisa Toscano Adamo; Ana Ballesteros-Gómez; Ariel Rodríguez-Torresi; Soledad Rubio; Mónica A. Nazareno (Journal of Plant Growth Regulation, 2026)

The threat of multidrug-resistant microorganisms: active surveillance of key antimicrobial resistant pathogens in 2025 - a report from the INVIFAR network - Adrián Martínez-Meléndez; Elvira Garza-González; María del Rosario Vázquez-Larios; Melissa Garibaldi-Rojas; Bernardo Alfonso Martinez-Guerra; Christian Daniel Mireles-Davalos; Samuel Pavel Escalante-Armenta; José Manuel Feliciano-Guzmán; Daniel Romero-Romero; Maria del Consuelo Velazquez-Acosta; Sandra Quintana-Ponce; Shaúl Ariel Navarro-Lara; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose Systematic collection and analysis of antimicrobial resistance data from key bacterial pathogens is essential to contribute to control antimicrobial resistance (AMR). The aim of this work was to survey the drug resistance on clinically relevant organisms stratified according to age, gender, clinical specimens and facilities. Methods Microbiological data were collected from 55 centers across 24 states in Mexico between January 1 and March 31, 2025. Bacterial identification and antimicrobial susceptibility testing were performed at each participating center using locally available methods. Data was processed using WHONET 2025. Isolates obtained from lower respiratory specimens, urine, blood, biopsies and abscesses were analyzed. Carbapenem non-susceptible isolates were further analyzed by PCR for common carbapenemase-encoding genes. Resistance frequencies were compared using the chi-square test. Results A total of 11,290 clinical isolates were analyzed, mostly from urine ( n = 7,149; 63.3%), followed by blood ( n = 1,370; 12.1%). The most prevalent was Escherichia coli ( n = 6,185; 54.8%), followed by Klebsiella pneumoniae ( n = 1,365; 12.1%) and Pseudomonas aeruginosa ( n = 1,110; 9.8%). Resistance to carbapenems in E. coli was higher in respiratory isolates (imipenem: 5.8%, p = 0.016; meropenem: 5.3%, p < 0.001), with 75.9% producing extended-spectrum ß-lactamases (ESBLs). K. pneumoniae had the highest resistance to ampicillin/sulbactam (52.5%, p = 0.028) and sulfamethoxazole/trimethoprim (62.1%, p = 0.014) in blood isolates, and 63.2% were ESBL-producers ( p = 0.001). In P. aeruginosa , urine isolates showed significantly higher resistance to ceftolozane-tazobactam (24.7%, p = 0.008), ceftazidime-avibactam (36.6%, p < 0.001), and meropenem (34.5%, p = 0.009) compared to other clinical specimens included. For A. baumannii , respiratory isolates had 73.6% resistance to meropenem ( p < 0.001). S. aureus from blood showed 25.7% resistance to oxacillin ( p < 0.004). The most frequent carbapenemase genes were bla OXA−48−like in E. coli (26/56, 46.4%), bla NDM for K. pneumoniae (7/17, 41.2%), bla OXA−24 in A. baumannii (79/108, 73.1%) and bla IMP for P. aeruginosa (18/108, 16.7%). Conclusion This surveillance study underscores the elevated levels of antimicrobial resistance, ESBL production, and carbapenemase activity among priority pathogens, including some Enterobacterales , P. aeruginosa , and A. baumannii . These findings emphasize the urgent need to strengthen epidemiologic surveillance programs in Mexican healthcare settings.

PreserVamos : Ecological data on aquatic ecosystems in Argentina collected through citizen science monitoring - Joaquín Cochero; Alejo Fabián Bonifacio; María Agostina Pecile; Micaela Zambrano; María Belén Sathicq; María Mercedes Nicolosi Gelis; Micaela Ailén Mujica; Milagros Bengolea; Marina Tagliaferro; Juan Manuel Brito; María Laura Ballesteros; Andrea Hued; et al. (Ecology, 2026)
Freshwater ecosystems are among the most threatened globally, yet remain under‐monitored in many regions, particularly in South America. Traditional monitoring approaches, while scientifically rigorous, are often limited by logistical, financial, and institutional constraints. While several citizen science initiatives have advanced freshwater habitat assessment in Europe (e.g., FreshWater Watch) and North America (e.g., EPA's Volunteer Monitoring Program), comparable efforts remain scarce in South America. PreserVamos contributes to filling this regional gap by providing the first large‐scale, standardized citizen‐generated dataset for aquatic ecosystems in Argentina, offering valuable opportunities for integration with global freshwater monitoring databases. “PreserVamos” is a citizen science initiative designed to collect and integrate ecological observations of rivers, lagoons, wetlands, estuaries, and streams throughout Argentina, where participants engage through a mobile application to record semiquantitative ecological indices, environmental conditions, human uses, and wildlife presence. Data are standardized through predefined survey forms and geolocated using mobile GPS. The calculated habitat index is supported by up to 25 complementary variables and a precision score estimating response reliability and is based on published riverine habitat indices for the country. To date, PreserVamos includes over 1200 observations from diverse waterbodies and biogeographic regions in the country, and an additional dataset is included with ~100 observations from other countries. Streams and rivers from the “sierras” (low mountain ranges) were among the most frequently sampled systems ( n = 312) and exhibited the highest ecological quality, with a mean index of 78.38 ± 9.45 (SD) on a scale of 0–100. Mountain streams ( n = 55) also showed high ecological scores, averaging 70.36 (±6.75). In contrast, estuaries ( n = 34) demonstrated lower ecological quality, with a mean index of 61.89 (±15.03). Lowland rivers ( n = 558), the most represented waterbody type, had a moderate mean index of 68.57 (±18.89). Lowland lagoons or lakes ( n = 228) showed lower ecological conditions, with an average score of 62.90 (±14.82). Patagonian forest lakes ( n = 29) had a high mean index of 78.34 (±11.06), while Patagonian Forest rivers ( n = 12) showed moderate conditions at 69.20 (±9.40). Patagonian steppe rivers were only represented by two observations, with a preliminary mean of 74.15 (±9.40). The dataset provides a unique opportunity to analyze spatial and seasonal ecological trends, assess the effectiveness of citizen science in environmental monitoring, and inform ecosystem management. This dataset is published under a Creative Commons Attribution 4.0 International License (CC‐BY 4.0). Users may reuse the dataset with proper citation.

Supramolecular solvent extraction of drugs and pharmaceuticals in indoor dust from public buildings - Cristina de Dios-Pérez; Ana Ballesteros-Gómez; Joaquín Ballesteros; Soledad Rubio (Science of The Total Environment, 2025)

Comprehensive characterization of organic compounds in indoor dust after generic sample preparation with SUPRAS and analysis by LC-HRMS/MS - Ana Ballesteros-Gómez; Joaquín Ballesteros; Soledad Rubio (Science of The Total Environment, 2024)

Supramolecular solvent extraction and ambient mass spectrometry for the determination of organic contaminants in food packaging material - María Jesús Dueñas Mas; Cristina de Dios-Pérez; Anad Ballesteros-Gómez; Soledad Rubio (Chemosphere, 2023)

The impact of physical fitness, social life, and cognitive functions on work ability in middle-aged and older adults - Jennifer A. Rieker; Patrick D. Gajewski; José Manuel Reales; Soledad Ballesteros; Klaus Golka; Jan G. Hengstler; Edmund Wascher; Stephan Getzmann (International Archives of Occupational and Environmental Health, 2023)
Objective Demographic changes encompass societies to maintain the work ability (WA) of aging workforces. The present study explored the relationship between modifiable lifestyle factors, cognitive functions, and their influence on WA, using a multi-group structural equation approach. Method Cross-sectional data from 247 middle-aged and 236 older employees from the Dortmund Vital Study were included in this analysis. We proposed a model with three exogenous variables (Physical Fitness, Cognitive Functions, and Social Life), and with WA as the endogenous variable. WA was measured with the Work Ability Index (WAI), which considers job demands and individual physical and mental resources. Multi-group analyses were based on the principles of invariance testing and conducted using robust estimation methods. Results Results revealed that Social Life outside work had significant positive effects on WA in both, middle-aged and older adults. Physical Fitness had a significant effect on WA only in middle-aged adult, and Cognitive Functions had no significant influence on WA in either group. In older adults, Physical Fitness correlated with Cognitive Functions, whereas in middle-aged adults, Cognitive Functions marginally correlated with Social Life. Conclusions Our results underline the importance of an active social life outside the workplace for WA, regardless of the employees’ age. The influence of Physical Fitness on WA changes with increasing age, indicating the necessity to have a differentiated view of age effects and interacting influencing factors. Our research contributes to the knowledge of how WA could be most effectively promoted in different age groups. Clinicaltrials.gov NCT05155397; https://clinicaltrials.gov/ct2/show/NCT05155397 .

Characterization of a new sustainable supramolecular solvent and application to the determination of oxy-PAHs in meat, seafood and fish tissues - María Jesús Dueñas-Mas; Ana Ballesteros-Gómez; Soledad Rubio (Food Chemistry, 2023)

Word-stem priming and recognition in type 2 diabetes mellitus, Alzheimer’s disease patients and healthy older adults - María Teresa Redondo; José Luís Beltrán-Brotóns; José Manuel Reales; Soledad Ballesteros (Experimental Brain Research, 2015)

Selective attention modulates visual and haptic repetition priming: effects in aging and Alzheimer's disease - Soledad Ballesteros; José M. Reales; Julia Mayas; Morton A. Heller (Experimental Brain Research, 2008)